Study of proinflammatory markers, galectin-3 level, lipid metabolism parameters, cardiovascular status and their relationship in patients with lymphomas before antitumor therapy - I. Ya. Sokolova; S. A. Kardovskaya; E. Yu. Salakheeva; Yu. Yu. Kirichenko; E. A. Siderko; O. V. Bochkarnikova; A. A. Shchendrygina; Yu. N. Belenkov; I. S. Ilgisonis (Кардиоваскулярная терапия и профилактика)
Aim. To study the significance of proinflammatory markers, galectin-3 levels, lipid profile parameters, cardiovascular status and their relationship in patients with lymphomas before the start of specific antitumor therapy, as well as to compare the studied parameters with patients with similar cardiovascular status without cancer.Material and methods. The study included 2 following groups of patients: the main group (n=30) — patients with newly diagnosed lymphoproliferative disease (LPD), the comparison group (n=30) — patients with similar risk factors and/or proven cardiovascular pathology and without cancer. All patients included in the study underwent determination of inflammation markers, lipid profile and special markers (concentration of interleukin-6 (IL-6) and galectin-3).Results. The patients of both groups included in the study were comparable in age, sex, risk factors for cardiovascular diseases, cardiovascular therapy. In patients of the main group, the level of potentially proatherogenic lipids in the group of patients with lymphomas was slightly higher than in the comparison group, although the differences did not reach statistical significance (p>0,05); the levels of acute phase proteins (C-reactive protein, ferritin, fibrinogen), erythrocyte sedimentation rate (p<0,05 for all parameters), IL-6 (p=0,032), galectin-3 (p=0,001) were significantly higher. Intragroup analysis in the LPD group using International Prognostic Index (IPI), Mantle cell Lymphoma International Prognostic Index (MIPI) and Follicular Lymphoma International Prognostic Index depending (FLIPI) demonstrated that the levels of galectin-3 and IL-6 were higher in patients with the worst prognosis indices. The correlation analysis revealed a direct moderate relationship between galectin-3 and IL-6 (r=0,488; p=0,016).Conclusion. The study showed that the study groups did not differ significantly in terms of the level of potentially proatherogenic lipids. The results of the comparative analysis demonstrate that the concentration of galectin-3 and IL-6 in LPD is significantly higher than in the comparison group; their high level may reflect the activity of the tumor process. The significance of these biomarkers in the development of cardiovascular toxicity complications in patients with LPD has not yet been studied and seems interesting from the point of view of their possible predictive role for cardiovascular complications of chemotherapy.